2012
DOI: 10.1158/1078-0432.ccr-12-1983
|View full text |Cite
|
Sign up to set email alerts
|

p53 Arg72Pro Polymorphism, HPV Status and Initiation, Progression, and Development of Cervical Cancer: A Systematic Review and Meta-Analysis

Abstract: Cervical cancer develops through progression from normal cervical epithelium through squamous intraepithelial lesions (SIL) to invasive cancer. Cervical cancer is associated with oncogenic human papillomavirus (HPV). The HPV E6 oncoprotein binds to the tumor suppressor gene product p53, promoting its degradation; the Arg allele of p53 Arg72Pro polymorphism binds more ardently with HPV E6 than the Pro variant. Here we evaluate the role of p53 Arg72Pro polymorphism and HPV status on the initiation, progression, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 50 publications
2
42
0
1
Order By: Relevance
“…Consistent with our results, Hu et al21 also reported that the TP53 G72 (Arg) was significantly overtransmitted in Caucasian CxCa subjects of a family‐based association study where HPV was determined, especially in subjects who were infected with HPV16/18 21. In validation of our results, a systematic meta‐analysis including 49 studies showed that HPV‐positive patients had significantly elevated odds of progression from squamous intraepithelial lesions to invasive CxCa when associated with the p53 Arg allele (OR, 1.37; 95% CI, 1.15‐1.62; P  < .001) that was not seen in HPV‐negative individuals 25. The authors further stated that the Arg allele of p53 codon 72 is associated with the progression from squamous intraepithelial lesions to CxCa in the presence of HPV positivity only.…”
Section: Discussionsupporting
confidence: 66%
“…Consistent with our results, Hu et al21 also reported that the TP53 G72 (Arg) was significantly overtransmitted in Caucasian CxCa subjects of a family‐based association study where HPV was determined, especially in subjects who were infected with HPV16/18 21. In validation of our results, a systematic meta‐analysis including 49 studies showed that HPV‐positive patients had significantly elevated odds of progression from squamous intraepithelial lesions to invasive CxCa when associated with the p53 Arg allele (OR, 1.37; 95% CI, 1.15‐1.62; P  < .001) that was not seen in HPV‐negative individuals 25. The authors further stated that the Arg allele of p53 codon 72 is associated with the progression from squamous intraepithelial lesions to CxCa in the presence of HPV positivity only.…”
Section: Discussionsupporting
confidence: 66%
“…A number of studies have focused on the molecular and cellular changes that occur during the initiation and progression of lung cancer. However, the gene polymorphisms involved, which are closely associated with the tumorigenesis and invasion of lung cancer, remain unclear (2)(3)(4). Therefore, it is essential to investigate effective lung cancer biomarkers at the early stages of disease and identify novel targets for the treatment of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The process of invasion and metastasis of tumor cells is complex, including a series of interactions amongst tumor cells and between tumor cells, host cells and extracellular matrixes. In particular, the involvement of multiple cytokines in cell regulation allows for metastasis and rapid growth of tumor cells (24,25). OPN is one such cytokine, and functions as a secretory multi-functional phosphorylated sialoglycoprotein and a non-collagenic adhesion molecule in the extracellular matrix (26).…”
Section: Discussionmentioning
confidence: 99%